A Culture and Coercion in Context: A Case Study of the Trafficking of Women in Indramayu - Nining; Riyady, Slamet (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the phenomenon of female trafficking in Indramayu within the framework of interactions between local culture and economic compulsion. Indramayu is known as one of the regions with a high rate of female migrant worker deployment, some of whom become entangled in human trafficking practices. The aim of this research is to understand how cultural values, economic pressures, and weak legal protections contribute to this cycle of exploitation. Using a qualitative approach and case study method, data were collected through field observations and document analysis. The findings reveal that female trafficking in Indramayu is driven not solely by economic factors, but also by social norms that tolerate or even support the migration of women abroad for livelihood reasons. Within a context of limited options and deeply rooted gender inequality, women often lack full agency over their migration decisions. This study highlights the importance of policy interventions that go beyond economic aspects, advocating instead for cultural transformation and the strengthening of protections for women's rights.